2021
DOI: 10.1177/10998004211025641
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Prediction Models for Preterm Birth Using CHARMS

Abstract: Objective: This study sought to evaluate prediction models for preterm birth (PTB) and to explore predictors frequently used in PTB prediction models. Methods: A systematic review was conducted. We selected studies according to the PRISMA, classified studies according to TRIPOD, appraised studies according to the PROBAST, and extracted and synthesized the data narratively according to the CHARMS. We classified the predictors in the models into socio-economic factors with demographic, psychosocial, biomedical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(165 reference statements)
0
9
0
Order By: Relevance
“…A single predictor may be weak in predicting preterm birth, while a better prediction can be obtained by combining a predictive model of multiple predictors [ 9 ]. Kim et al conducted a systematic review summarizing current predictive models for predicting the risk of preterm birth [ 10 ]. The area under the receiver operating characteristic curve (AUC) for predicting preterm birth in these studies varied from 62 to 80%, and the effect of prediction was related to the number of predictors, populations, and the period of data (the first trimester, second trimester, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…A single predictor may be weak in predicting preterm birth, while a better prediction can be obtained by combining a predictive model of multiple predictors [ 9 ]. Kim et al conducted a systematic review summarizing current predictive models for predicting the risk of preterm birth [ 10 ]. The area under the receiver operating characteristic curve (AUC) for predicting preterm birth in these studies varied from 62 to 80%, and the effect of prediction was related to the number of predictors, populations, and the period of data (the first trimester, second trimester, etc.)…”
Section: Introductionmentioning
confidence: 99%
“… 21 Previous systematic reviews from other research teams showed that there are high ROB and suboptimal reporting quality in prediction models in oral health and preterm birth. 22 , 23 To date, there has been limited data for evaluating the quality of existing IPF prognostic models; therefore, in this cross-sectional study, we assessed IPF prognostic models with PROBAST and TPRIPOD checklists, aiming to identify the ROB and reporting quality of these studies and highlight the strengths and limitations of the methodologies of IPF prognostic models.…”
Section: Introductionmentioning
confidence: 99%
“…Initial applications of ML techniques have assisted experts in better predicting PTB [28,30]. Studies have continuously used updated ML techniques on a more diverse obstetric population to extract generalizable PTB predictors [18,[31][32][33]. Such efforts proved to have the potential to significantly benefit women's and children health by identifying significant risk factors [34].…”
Section: Introductionmentioning
confidence: 99%